2011
DOI: 10.1159/000334738
|View full text |Cite
|
Sign up to set email alerts
|

Drug Interaction in Psycho-Oncology: Antidepressants and Antineoplastics

Abstract: Background and Objectives: Although there is a growing impact of psychiatric and depressive disorders in cancer patients, literature on the idiosyncrasies of antidepressants (ADs) used in those conditions and their interactions with antineoplastic agents (ANs) is scarce. Sharing the same biotransformation pathways enhances the risk of drug interaction between ADs and ANs, specifically when compounds are inducers, inhibitors or substrates of cytochrome P450 (CYP 450). In cancer patients, such drug interactions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(40 citation statements)
references
References 54 publications
1
36
0
1
Order By: Relevance
“…A phase I trial was conducted to assess PK interactions between ipilimumab and dacarbazine or carboplatin/paclitaxel chemotherapy used for melanoma . Ipilimumab, a CTLA‐4–targeted ICI, induces cytokines (e.g., IL‐1, IL‐2, interferon‐β, and IL‐6) that modulate the activity of CYP enzymes, potentially altering the PK/PD of dacarbazine and paclitaxel that are metabolized by CYP1A2/2E1 and CYP2C8/3A4, respectively . The study found that the estimated fold changes in geometric mean ratios (GMRs) for peak concentration (C max ) and area under the curve (AUC) of ipilimumab when administered with dacarbazine were 0.982 and 0.917, respectively.…”
Section: Treatment Selectionmentioning
confidence: 99%
“…A phase I trial was conducted to assess PK interactions between ipilimumab and dacarbazine or carboplatin/paclitaxel chemotherapy used for melanoma . Ipilimumab, a CTLA‐4–targeted ICI, induces cytokines (e.g., IL‐1, IL‐2, interferon‐β, and IL‐6) that modulate the activity of CYP enzymes, potentially altering the PK/PD of dacarbazine and paclitaxel that are metabolized by CYP1A2/2E1 and CYP2C8/3A4, respectively . The study found that the estimated fold changes in geometric mean ratios (GMRs) for peak concentration (C max ) and area under the curve (AUC) of ipilimumab when administered with dacarbazine were 0.982 and 0.917, respectively.…”
Section: Treatment Selectionmentioning
confidence: 99%
“…Con pacientes oncológicos sometidos a varias quimioterapias, es importante tener precaución con las interacciones farmacológicas. Antidepresivos como la fluoxetina, la sertralina, la paroxetina y la fluvoxamina inhiben la transformación de agentes antineoplásicos a través del CYP450 3A4, lo que produce una disminución de su eficacia o mayor toxicidad de los mismos 35 . Otros fármacos como el citalopram, el escitalopram, la venlafaxina y la mirtazapina son inhibidores débiles, lo que los convierte en una elección más segura 35 .…”
Section: Modalidades De Tratamiento Psicofarmacologíaunclassified
“…The mourning of current and anticipated losses, the fear of death, concerns with the loved ones, the effect of some chemotherapeutics in mood and biological characteristics of the tumor [1] have been implicated in the genesis of this suffering. According to the literature, about 50% of these patients are people with mental illness, mainly adjustment disorders (4-35%) followed by major depressive disorder (3-36%) [3,[4][5][6] and, for some authors, delirium [7]. However, only 30% of the clinical psychiatric syndromes associated with cancer are identified by their doctors [8].…”
Section: Introductionmentioning
confidence: 99%
“…Depression is associated with lower quality of life, increased subjective perception of pain, suicidal thoughts, wish for hastened death and a worse prognosis [3,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation